1996
DOI: 10.1089/vim.1996.9.89
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antibody Reactivity to Synthetic Peptides from Different Parts of the Hepatitis C Virus Genome

Abstract: Infection by hepatitis C virus (HCV)*, the aetiologic agent responsible for the majority of non-A-non-B posttransfusion hepatitis, is detected by assaying for antibodies against structural and nonstructural recombinant proteins or synthetic peptides. The aim of this study was to characterize the antibody reactivity of selected sera against antigenic peptides spanning immunodominant regions of the core, NS4 and NS5 HCV proteins. Reactivity to synthetic peptides was determined by enzyme immunoassay (EIA) for 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…4B) and several antigenic amino acids within it. The NS5 antigenic region 2251-2260 identified in this study has not been previously reported in literature, although several other NS5 epitopes have been identified Khudyakov et al, 1995;Pujol et al, 1996].…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…4B) and several antigenic amino acids within it. The NS5 antigenic region 2251-2260 identified in this study has not been previously reported in literature, although several other NS5 epitopes have been identified Khudyakov et al, 1995;Pujol et al, 1996].…”
Section: Discussionmentioning
confidence: 47%
“…Both sequences of Prezzi et al [1996] differ from the seven we have identified, although their second sequence is outside the scope of our affinity-purified antibody selection method, since our NS4 protein fragment encompasses only 1644-1812 amino acid residues. The HCV core protein has been well characterised antigenically using synthetic peptides, especially its Nterminal part [Okamoto et al, 1992;Goeser et al, 1994;Sallberg et al, 1994;Prezzi et al, 1996;Pujol et al, 1996]. The fact that it is possible to map core antigenic determinants using short peptides suggests a rather linear character for core epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many attempts have been made to improve the HCV serodiagnosis. Studies of the HCV antigenic structure have allowed construction of diagnostic systems with improved assay specificity and sensitivity [Krajden, 1995;Roggendorf et al, 1996] The antigenic structure of HCV proteins has been studied using synthetic peptides [Okamoto et al, 1992;Simmonds et al, 1993;Goeser et al, 1994;Zhang et al, 1994;Bhattacherjee et al, 1995;Khudyakov et al, 1995;Pujol et al, 1996;Sallberg et al, 1996] and short HCV polypeptides expressed in prokaryotic systems [Goeser et al, 1994;Mondelli et al, 1994;Claeys et al, 1995].…”
Section: Introductionmentioning
confidence: 99%